2012
DOI: 10.1016/j.acap.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Children with Special Health Care Needs in School and the Community

Abstract: Objective Children with special health care needs (CSHCN) are at risk for decreased participation which can negatively impact their lives. The objectives of this study were to document the presence of participation restrictions for CSHCN compared to other children and to determine how personal and environmental factors are associated with participation restrictions for CSHCN. Methods The 2007 National Survey of Children’s Health (NSCH) was analyzed to evaluate two participation outcomes for children aged 6–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Self-perceived pain and the items PSCH/PLTF (proxy for disease's severity) were the significant clinical variables impacting HRQoL, whereas SCL, RES, SR and SSSS were the most significant psychosocial ones. These findings are in accordance with literature, which indicated that perceptions of HRQoL could be influenced by several factors (The KIDSCREEN Group Europe, 2006;Ravens-Sieberer et al, 2001;2005;Houtrow et al, 2012. Also reinforce the suggestions in the literature to assess both disease related and non-disease-related factors (Sawyer et al, 2001), including physical, psychological and social perspectives (WHO, 2012), as well as limitations in ordinary activities (Denny et al, 2014;van der Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Self-perceived pain and the items PSCH/PLTF (proxy for disease's severity) were the significant clinical variables impacting HRQoL, whereas SCL, RES, SR and SSSS were the most significant psychosocial ones. These findings are in accordance with literature, which indicated that perceptions of HRQoL could be influenced by several factors (The KIDSCREEN Group Europe, 2006;Ravens-Sieberer et al, 2001;2005;Houtrow et al, 2012. Also reinforce the suggestions in the literature to assess both disease related and non-disease-related factors (Sawyer et al, 2001), including physical, psychological and social perspectives (WHO, 2012), as well as limitations in ordinary activities (Denny et al, 2014;van der Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Such findings suggest a dynamic interdependence between these different variables, as stressed out in the literature (The KIDSCREEN Group Europe, 2006;Houtrow et al, 2012;Ravens-Sieberer et al, 2001;2005), although pointing out a higher relevance of non-disease-related factors. Thus, these results support the suggestions in the literature emphasizing more the importance to focus on the disease's impact on psychosocial dimensions, and less on the diagnostic categories/physical dimensions (Denny et al, 2014;Mackner et al, 2012;van der Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Isolation leads to many negative outcomes for families and youth with disabilities, including low levels of socialemotional support. 17 In many cases, there simply are not mechanisms for supporting their inclusion and engagement. Transportation only makes this lack of availability worse for individuals residing in rural communities.…”
Section: Discussionmentioning
confidence: 99%
“…declining social activity) for those living with a disability. [7][8][9][10][11][12][13][14] Aside from the actual disability or type of injury, a decline in social activity may result from fatigue, 9,11 unfavorable weather conditions (e.g. excessive cold or heat, snow, etc.…”
Section: Introductionmentioning
confidence: 99%